Analysis of Spatial Characteristics and Influencing Factors of Water and Soil Erosion in Nine Plateau Lake Basins in Yunnan Province - WANG Juan; LIU Xiaolin; JIN Pingwei; SHI Yandong; ZHOU Ruipeng; WU Zhenyu; ZHANG Churan; HUANG Hairong (Renmin Zhujiang)
Soil and water erosion monitoring and evaluation can provide a scientific basis for preventing and controlling soil and water erosion disasters and conducting regional soil and water conservation planning and ecological environment construction. On the basis of the CSLE model,the factors and characteristics of soil and water erosion in nine plateau lake basins in Yunnan Province are analyzed by means of remote sensing analysis,field investigation,model calculation, and technical standards such as Standards for Classification and Gradation of Soil Erosion (SL 190—2007).In 2021,the water and soil erosion area was 1 306.92 km2,accounting for 16.67% of the total land area.In terms of land use type,the water and soil erosion area was mainly distributed in forest land and cultivated land,which accounted for 35.69% and 31.60% of the water and soil erosion area in the nine basins,respectively,with light erosion as the main form.The area with intense and extremely intense erosion mainly focused on the cultivated land,accounting for 82.85% of that in the nine basins.In the nine plateau lake basins,the main controlling factor affecting water and soil erosion of cultivated land and construction land is slope,while the main controlling factors affecting soil and water erosion in gardens,forest land,and grassland are vegetation coverage and slope.According to the characteristics of soil and water erosion in the nine basins,the forest land needs to be protected and equipped with a vegetation system dominated by soil and water conservation forests and water conservation forests,and measures such as enclosure and protection of distant mountains should be strengthened.The cultivated land,especially the sloping land, shall be comprehensively controlled in terms of soil and water erosion.By obtaining the spatial distribution characteristics of water and soil erosion in the nine basins,the study can grasp the land use types with water and soil erosion occurring frequently in the basins and provide support for the comprehensive management of water and soil erosion.